Hispania, A journal devoted to the teaching of Spanish and Portuguese, published by the American Association of Teachers of Spanish and Portuguese, Los Angeles (California), University of Southern California, vol. 69, núms. 3 y 4 de 1986. - Valencia Zuluaga, José Néstor (Thesavrvs, 2023)
Reseña de revistas.